Using Auto Regressive Distributed Lag Model (ARDL) to Measuring Determinants of Economic Growth in Sudan – Statistical and Standard study for the period (1990- 2020) - Fatur, Hassan Ali Osman; Saad, Sofian Abuelbacher Adam (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aims to examine the long-term relationship between (Governmental expending, Exports, Unemployment, Inflation, Investment) and Economic growth in Sudan. The study has used statistical method using tools of econometrics in analysis, it has used the method of co-integration, Error Correction Model and Granger causality test to estimate the relationship between variables. The results showed that there is a correlation between the variables. The variables are also integrated in the firstly stage. The results also showed an existence of a negative relationship between governmental expending, unemploment, inflation and economic growth, and a positive relationship between exports, investment and economic growth. The study findings out that increase inflation rate with 1% that leads to a decrease in economic growth rates by 0,6%. the most important recommendations are applying relevance and effective economic policies, in order to control the inflation which directly effecting on the economic growth, and study the fluctuations and foresee the rate of inflation to mitigate its effects.